Observation and isolation of layered and framework ytterbium hydroxide phases using in situ energy-dispersive X-ray diffraction - McIntyre, Laura J.; Prior, Timothy J.; Fogg, Andrew M. (Chemistry Of Materials, 2010)
In situ energy-dispersive X-ray diffraction has been used to investigate the synthesis of the recently reported lanthanide hydroxynitrate phases, Ln 2 (OH) 5 NO 3 ·1.5H 2 O (Ln = Y, Er, Yb). Through control of the reaction temperature, three distinct layered phases with differing degrees of hydration (x = 1 (1), 1.5 (2), and 2 (3)) were observed in the Yb synthesis and subsequently isolated. Only the phase with x = 1.5 was observed for the reactions with Y and Er. The crystal structures of Yb 2 (OH) 5 NO 3 2H 2 O (2) and Yb 2 (OH) 5 NO 3 H 2 O (3) were determined in a single-crystal diffraction study and represent the first crystal structures of the new lanthanide hydroxynitrate phases. Both Yb 2 (OH) 5 NO 3 ·2H 2 O and Yb 2 (OH) 5 NO 3 ·H 2 O adopt orthorhombic structures in which the nitrate anion is coordinated to the Yb 3+ cations within the hydroxide layer and are largely resistant to anion exchange. This is in contrast to the Ln 2 (OH) 5 NO 3 ·1.5H 2 O phases, which undergo facile anion exchange reactions at room temperature, indicating that the nitrate resides in the interlayer gallery. At temperatures above 200 °C, the three layered phases were determined to be intermediates in the synthesis of Yb 4 O(OH) 9 NO 3 (4), which has a framework structure with the uncoordinated nitrate anions located in one-dimensional channels. The in situ diffraction technique has allowed for a detailed kinetic and mechanistic investigation of the synthesis and revealed that the layered ytterbium hydroxynitrate phases form via a two-dimensional phase boundary-controlled growth mechanism. It was also possible to estimate the activation energies for the hydrothermal synthesis of Yb 2 (OH) 5 NO 3 ·H 2 O and Yb 2 (OH) 5 NO 3 ·2H 2 O from basic solution, as +29 and +67 kJ/mol, respectively. © 2010 American Chemical Society.
Keywords: Materials Chemistry; General Chemistry; General Chemical Engineering